Energy performance of vertical extensions on old buildings: comparison between architectural membranes and conventional building technologies - Mendonça, Paulo (2020)
This research aims evaluating in what measure the proposed refurbishment solutions with architectural membranes can benefit an existing building and provide an energy efficient alternative to conventional reference building technologies for vertical extensions. In order to do it, an old building from the 19th century, located in Porto (Portugal) is taken as case study. Both solutions are compared regarding thermal comfort, energy consumption for heating/cooling needs using numerical simulation, which allowed evaluating the project from the environmental point of view, based on the energy consumption. The proposed membrane alternatives include conventional and non-conventional thermal/acoustic insulation and a membrane envelope option with vegetation on its external skin. The paper argues that architectural membrane refurbishment solutions can constitute an energy efficient alternative to lightweight conventional ones.